2017
DOI: 10.3390/ijerph14101161
|View full text |Cite
|
Sign up to set email alerts
|

Higher Mortality in Trauma Patients Is Associated with Stress-Induced Hyperglycemia, but Not Diabetic Hyperglycemia: A Cross-Sectional Analysis Based on a Propensity-Score Matching Approach

Abstract: Background: Stress-induced hyperglycemia (SIH) is a form of hyperglycemia secondary to stress and commonly occurs in patients with trauma. Trauma patients with SIH have been reported to have an increased risk of mortality. However, information regarding whether these trauma patients with SIH represent a distinct group with differential outcomes when compared to those with diabetic hyperglycemia (DH) remains limited. Methods: Diabetes mellitus (DM) was determined by patient history and/or admission glycated hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 30 publications
6
26
1
Order By: Relevance
“…The above adjustments are expected to reduce bias in the assessment of mortality outcomes and infer a different extent of the odds of mortality. An adjustment to reduce bias in comparison is important during the assessment; for example, our previous study which explored the morbidities associated with SIH for all trauma patients had revealed that even the SIH had a 2.9-fold higher odds of pneumonia (95% CI 1.68–4.93; p < 0.001) and a 4.8-fold higher odds of acute renal failure (95% CI 2.15–10.52; p < 0.001) than the NDN, there were no differences in the rates of pneumonia and acute renal failure between SIH and NDN after adjustment by propensity-score matching [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The above adjustments are expected to reduce bias in the assessment of mortality outcomes and infer a different extent of the odds of mortality. An adjustment to reduce bias in comparison is important during the assessment; for example, our previous study which explored the morbidities associated with SIH for all trauma patients had revealed that even the SIH had a 2.9-fold higher odds of pneumonia (95% CI 1.68–4.93; p < 0.001) and a 4.8-fold higher odds of acute renal failure (95% CI 2.15–10.52; p < 0.001) than the NDN, there were no differences in the rates of pneumonia and acute renal failure between SIH and NDN after adjustment by propensity-score matching [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This second definition, based on similar percentages of glucose elevation, both in patients with and without diabetes, is more reasonable, because the admission glucose level is at 1.3-fold of ADAG, in both patients with and without diabetes with a similar severity of injury in this study. Under the hypothesis that stress presumably caused a similar percentage of glucose increase both in patients with and without diabetes, in the second definition (glucose level of ≥300 mg/dL), the SIH in DM had a 3-fold higher odds of adjusted mortality than DN, which is comparable with the 3-fold adjusted mortality of SIH in patients without diabetes, compared to NDN [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…SIH is attributed to a state of excess hepatic glucose output, diminished insulin production, and insulin resistance in the peripheral tissues, with excessive adrenal cortical output and high circulating levels of cytokines [ 5 , 6 ]. The prevalence of SIH has been reported as 4% [ 7 ] and 4.9% [ 8 ] of patients with all trauma causes to 7.8% of patients with isolated moderate to severe trauma brain injuries [ 9 ] and up to 48.9% of patients with a hip fracture [ 10 ]. It is also associated with increased in-hospital mortality, especially in patients without diabetes [ 7 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations